The Influence of Cash, Cash Equivalents, Marketable Securities, and Financing on Liquid Assets at Bank Lampung - Kamelia; Erna Listyaningsih; Muhammad Irfan Pratama (International Journal of Management, Economic and Accounting, 2026)
This study aims to analyze the effect of cash, cash equivalents, marketable securities, and financing on liquidity assets at Bank Lampung. Liquidity is a crucial aspect in maintaining bank operational stability and the ability to meet short-term obligations. The data used in this study are monthly time series data obtained from Bank Lampung’s financial statements during the period 2020–2024. The analytical method employed is multiple linear regression using EViews software. Prior to hypothesis testing, the data were examined through stationarity tests and classical assumption tests, including normality, multicollinearity, heteroskedasticity, and autocorrelation tests. The results indicate that partially, cash, cash equivalents, marketable securities, and financing have an effect on liquidity assets. Simultaneously, all independent variables have a significant effect on the liquidity assets of Bank Lampung. These findings highlight the importance of proper asset composition management in maintaining bank liquidity. This study is expected to provide useful insights for Bank Lampung’s management in formulating effective liquidity asset management policies.